The Effectiveness of Caffeine Consumption on Cardiorespiratory Endurance Capacity, Motor Function, and Skill Performance of Athletes: A Secondary Data Analysis Study (Meta-Analysis) - Ibrahim Sembiring; Imam Fauzi Telaumbanua; Nasrulloh H arahap; Azizun Almauzaki Siregar; Aditya Rianda Harahap; Andes Martua Harahap (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Cardiorespiratory capacity and motor efficiency are crucial for athlete performance under extreme fatigue. This descriptive quantitative meta-analysis aims to analyze the effectiveness of caffeine as an ergogenic aid on physical and psychomotor performance. Secondary data were drawn from five reputable scientific literatures with controlled experimental designs in badminton, soccer, hockey, karate, and cognitive function. The synthesis of results shows that caffeine significantly increases aerobic endurance (p < 0.05), maintains skill stability under fatigue, and improves accuracy and reaction time. Neurophysiologically, caffeine blocks adenosine receptors in the central nervous system to delay the perception of fatigue and stimulates calcium release in the sarcoplasmic reticulum to strengthen muscle contractions. An optimal dose of 3–6 mg/kg body weight consumed 45–60 minutes before activity has been shown to be valid, legal, and effective in delaying central/peripheral fatigue and boosting performance by 2–3%. Further research is needed to examine the variability in individual responses based on genetics and caffeine habituation.